The Effect of Social Support on Pregnant Women Health in Minangkabau Matrilineal Communities - Devi Syarief1, Andi Zulkifli Abdullah2, Suriah3, Healthy Hidayanti4, Dewi Susilawati5, Ety Aprianti6 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This research aims to explore the effect of social support on the health of pregnant women in theMinangkabau matrilineal community, Indonesia, from the perspective of the husbands, community leaders,health cadres and workers.Method: This study employs qualitative research, while purposive sampling techniques were used to select51 informants comprising 18 husbands, 14 community leaders, eight medical workers, and 11 health cadres.In addition, the data collection method involved focus group discussions and in-depth interviews and wasanalyzed using content analysis.Results: The findings showed the social support of the Minangkabau matrilineal community towards pregnantwomen was non-optimal and was in the form of emotional, informative, and instrumental assistance.Conclusion: The improvement in the health status of pregnant women is achievable with an intervention toincrease social support, particularly in the Minangkabau matrilineal community, West Sumatra.